Pengaruh Kualitas Layanan Driver Terhadap Loyalitas Pelanggan Melalui Kepuasan Pengguna Jasa Gojek Online Di Kota Jember - Yusita Titi Hapsari; Shendy Andrie Wijaya; Intan Tri Novitas Sari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
Thisystudy aims to analyzepand find out the effect of service quality drivers on customer loyalty throughysatisfaction. Primary data obtained through questionnaires distributed to Gojek service users using Google Form. The population in this study is not limited in number. In this study, the sample used was 100 respondents who used Gojek services. This study uses 3 variables which are then analyzed using path analysis. From?the results of the t test research, namely the quality of service on satisfaction has a value of t count (1.819) t table (1.66) with a significance of 0.072 so that there is a significant effect. Analysis of t test data, namely the quality of service to customer loyalty has a value of t count (5.258) t table (1.66) with a significance of 0.000 so there is a significant effect. The t-test analysis is that satisfaction with customer loyalty has a value of t count (4.168) t table (1.66) with a significance of 0.000 so that there is a significant effect. From the results of the calculation of the sobel test of service quality on customer loyalty through the satisfaction of online Gojek service users in the city of Jember, it can be obtained a value of 2.274, because the z value obtained is greater than the t-table value (1.66), it can be concluded that satisfaction can indirectly mediate service quality customer loyalty